Human adipose‐tissue derived mesenchymal stem cells induce functional de‐novo regulatory T cells with methylated FOXP3 gene DNA. (4th July 2013) - Engela, A. U.; Hoogduijn, M. J.; Boer, K.; Litjens, N. H. R.; Betjes, M. G. H.; Weimar, W.; Baan, C. C.
Summary Due to their immunomodulatory properties, mesenchymal stem cells (MSC) are interesting candidates for cellular therapy for autoimmune disorders, graft‐versus‐host disease and allograft rejection. MSC inhibit the proliferation of effector T cells and induce T cells with a regulatory phenotype. So far it is unknown whether human MSC‐induced CD4+CD25+CD127–forkhead box P3 (FoxP3)+ T cells are functional and whether they originate from effector T cells or represent expanded natural regulatory T cells (nTreg). Perirenal adipose‐tissue derived MSC (ASC) obtained from kidney donors induced a 2·1‐fold increase in the percentage of CD25+CD127–FoxP3+ cells within the CD4+ T cell population from allostimulated CD25–/dim cells. Interleukin (IL)‐2 receptor blocking prevented this induction. The ASC‐induced T cells (iTreg) inhibited effector cell proliferation as effectively as nTreg. The vast majority of cells within the iTreg fraction had a methylated FOXP3 gene Treg‐specific demethylated region (TSDR) indicating that they were not of nTreg origin. In conclusion, ASC induce Treg from effector T cells. These iTreg have immunosuppressive capacities comparable to those of nTreg. Their induction is IL‐2 pathway‐dependent. The dual effect of MSC of inhibiting immune cell proliferation while generating de‐novo immunosuppressive cells emphasizes their potential as cellular immunotherapeutic agent.